Recent Developments in Metal-Based Drugs and Chelating Agents for Neurodegenerative Diseases Treatments - Sales, Thais A; Prandi, Ingrid G; Castro, Alexandre A de; Leal, Daniel H S; Cunha, Elaine F F da; Kuca, Kamil; Ramalho, Teodorico C (International journal of molecular sciences, 2019)
The brain has a unique biological complexity and is responsible for important functions in the human body, such as the command of cognitive and motor functions. Disruptive disorders that affect this organ, e.g. neurodegenerative diseases (NDDs), can lead to permanent damage, impairing the patients' quality of life and even causing death. In spite of their clinical diversity, these NDDs share common characteristics, such as the accumulation of specific proteins in the cells, the compromise of the metal ion homeostasis in the brain, among others. Despite considerable advances in understanding the mechanisms of these diseases and advances in the development of treatments, these disorders remain uncured. Considering the diversity of mechanisms that act in NDDs, a wide range of compounds have been developed to act by different means. Thus, promising compounds with contrasting properties, such as chelating agents and metal-based drugs have been proposed to act on different molecular targets as well as to contribute to the same goal, which is the treatment of NDDs. This review seeks to discuss the different roles and recent developments of metal-based drugs, such as metal complexes and metal chelating agents as a proposal for the treatment of NDDs.
Keywords: drug development; Humans; neurodegenerativní nemoci; přehodnocení terapeutických indikací léčivého přípravku; Metals; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Drug Repositioning; Molecular Docking Simulation; metallodrugs; lidé; kovy; zvířata; amyloidní beta-protein; vyvíjení léků; amyloid; simulace molekulární dynamiky; Amyloid; Amyloid beta-Peptides; Molecular Dynamics Simulation; chelátory; Neurodegenerative Diseases; Animals; chelating agents; Drug Development; Chelating Agents